Cortical auditory evoked potentials in unsuccessful cochlear implant users - Munivrana, Boška (Array, 2013)
In some cochlear implant users, success is not achieved in spite of optimal clinical factors (including age at implantation, duration of rehabilitation and post-implant hearing level), which may be attributed to disorders at higher levels of the auditory pathway. We used cortical auditory evoked potentials to investigate the ability to perceive and discriminate auditory stimuli in 10 unsuccessful implant users aged 8–10 years (CI) and 10 healthy age-matched controls with normal hearing (NH). Pure tones (1 and 2 kHz) and double consonant-vowel syllables were applied. The stimuli were presented in an oddball paradigm that required the subjects to react consciously. The latencies and amplitudes of the P1, N1, P2, N2 and P3 waves were analyzed, in addition to reaction times and number of responses. Significant differences in the average response times and number of responses were observed between the CI and NH groups. The latencies also indicate that the CI group took longer to perceive and discriminate between tonal and speech auditory stimuli than the NH group.